Magnetic resonance imaging of the wrist: Findings in elite gymnasts - Fredericson, M.; Matheson, G.; Ho, Ch.; Waite, B.; Peterson, J.; Williams, C. (Archives of Physical Medicine and Rehabilitation, 2004)
Objectives: To evaluate the wrists of asymptomatic elite gymnasts with magnetic resonance imaging (MRI) and to define better the range of "normal" findings in this select population. Design: Cohort study. Setting: Academic medical center. Participants: 11 elite collegiate gymnasts with normal physical examination and no history of wrist injury. Interventions: Not applicable. Main Outcome Measures: Grade of severity of pathology seen on MR images (0 [no pathology] to 3 [severe pathology]) of the following structures: ligaments, tendons, cartilage, and bony structures. Presence or absence of cysts and fluid collection and carpal tunnel changes. Results: All gymnasts studied (100%) demonstrated at least mild pathology in at least 4 of the 6 structures evaluated. All (N=11) had findings in the ligaments (18% mild, 82% moderate), tendons (45% mild, 55% moderate), and cartilage (64% mild, 27% moderate, 9% severe). Most demonstrated bony abnormalities (n=10, 55% mild, 27% moderate, 9% severe), presence of cysts and fluid collections (n=8, 73%), and carpal tunnel changes (n=7, 64%). Conclusions: MRI of asymptomatic elite gymnasts` wrists demonstrated findings that may be unique to this population. Care must be taken to correlate clinical history and physical examination with MRI findings